Physical load and referees` decision-making in sports games: A scoping review - Bloß, N.; Schorer, J.; Loffing, F.; Büsch, D. (Journal of Sports Science & Medicine, 2020)
Referees in sports games have a high level of responsibility as they have to make correct and appropriate decisions at any point during a match. Regarding referees` decision-making (RDM) as a perceptual-cognitive process, evidence suggests that physical load might reduce cognitive performance and thus might reduce RDM performance as well. In consideration of increasing game dynamics, referees have to cope with high physical load, but they have to make correct and appropriate decisions further on. Here, we review the current state of research on the relationship between physical load and RDM. A scoping review was performed, in accordance with the PRISMA guidelines, using the following databases: Scopus, PubMed, Web of Science (all databases), SURF and SPONET (both with an English and German search). Only primary studies written in English or German that investigated the relationship between physical load and RDM in sports games were included. Eleven studies included in the review investigated six physical parameters and RDM: match period, velocity, blood lactate, running time, heart rate, distance covered. Most findings of the studies showed no relationship between physical load and RDM (n = 18). Thirteen findings suggest a negative relationship and three findings indicate a positive relationship between physical load and RDM. Results of the scoping review show contradictory evidence across and within investigated different physical parameters. As RDM consists of multi-factorial components, it is recommended to conduct systematic research programs - field as well as experimental studies - to resolve the missing control of potential confounding variables and to consider the difference of internal and external load.